Increasing the Ability and Legal Awareness of the Tanah Merah Dajah Village Community Regarding Domestic Violent Crimes - Erma Rusdiana (Veteran Society : Jurnal Pengabdian Masyarakat, 2020)
AbstractTanah Merah Dajah Village is not too far from the city of Bangkalan, it does not mean that the community has enough information about many things. Limited access and varying levels of education, economic conditions and a wrong understanding of religion, socially there are quite serious problems in society, namely about violence in the household. Among the community, including in thevillage community, it Tanah Merah Dajah has become a kind of tradition or habit to cover up acts of violence, especially domestic violence (KDRT) experienced by women and children. Until now, the problem of domestic violence is still considered a disgrace. Even if some of the victims asked for help from village officials, this was done secretly and the purpose of reporting to village officials was to make peace. In practice, the village apparatus conducts mediation to bridge these problems, so that the problems do not spread out. The settlement by the Village Head did not end the domestic violence, but it often repeated itself. The understanding residents of Tanah Merah Dajah Village, Tanah Merah Sub-district regarding domestic violence as a form of crime prior to the implementation of the legal socialization program is still low. This can be seen from the perception of society that views domestic violence as a personal matter which is a disgrace and must be kept tightly, even with family.Keywords: Legal Awareness, Domestic, Violent, Crimes